Comparison of microbial isolates isolated from external ear canal of sheep and their susceptibility to antibiotics - Hayyawi, Sahar Mahdi (The Iraqi Journal of Veterinary Medicine, 2012)
One hundred sheep with bilateral otitis externa were studied one year and a half .Theexudates of both external ears obtained using sterile swabs, and microorganisms were isolatedaccording to standard microbiological techniques. There was bacterial and fungal growth inmany of the samples. The total numbers of isolates from right ear was 104 , and the mostcommon pathogens isolated in right ear were Staphylococcus aureus 30.76 % , thenStaphylococcus epidermidis 9.61% and Pseudomonas aeruginosa 9.61 % while E.coli ,Proteus mirabilis and Streptococcus pyogenes were 7.69% for each of them , Candidaalbicans 5.76% , Klebsiella pneumonia 3.84% ,Nocardia spp 3.84% , Pasteurella multucida3.84% ,Mannheimia haemolytica 3.84% , Aspergillus spp. 3.84 % and Streptomyces spp.1.23% . The total number of isolates from left ear was 96 ,the most pathogens wereStaphylococcus aureus 27.08% while Pseudomonas aeruginosa 12.5% and Streptococcuspyogenes were 12.5% , Klebsiella pneumonia 8.33 % and Proteus mirabilis 8.33 % ,Staphylococcus epidermidis , Nocardia spp 6.25 % , then Streptomyces spp , Pasteurellamultucida and Mannheimia haemolytica were 4.16% , the last E.coli , Aspergillus spp andCandida albicans were 2.08 % for each of them . The result were showed significantdifferences at level P ˂0.05 between bacteria and fungi isolates, and have no significantdifferences at level P˃ 0.05 between right and left ear . High susceptible rates of grampositive Staphylococcus aureus to (Amoxicillin + Clavulaunic acid) and Chloramphenicolwere 100 % , while high susceptible rates of gram negative Pseudomonas aeruginosa was90.90 % to Ciprofloxacin, (Amoxicillin+ Clavulaunic acid) and Chloramphenicol .